1998
DOI: 10.1093/emboj/17.12.3277
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin B (secretogranin I), a neuroendocrine-regulated secretory protein, is sorted to exocrine secretory granules in transgenic mice

Abstract: Chromogranin B (CgB, secretogranin I) is a secretory granule matrix protein expressed in a wide variety of endocrine cells and neurons. Here we generated transgenic mice expressing CgB under the control of the human cytomegalovirus promoter. Northern and immunoblot analyses, in situ hybridization and immunocytochemistry revealed that the exocrine pancreas was the tissue with the highest level of ectopic CgB expression. Upon subcellular fractionation of the exocrine pancreas, the distribution of CgB in the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This would require packaging of the maturase into the nascent micronemes where processing would occur in a manner akin to prohormone convertase processing of substrates in immature secretory granules (ISGs) (Molinete et al, 2000;Hook and Metz-Boutigue, 2002). A distinction here, however, is that ISGs are derived from condensing vacuoles that bud from the TGN (Natori et al, 1998). Alternatively, if the proTgM2AP-positive compartment is distinct from early endosomes, its juxtaposition suggests that it might be the equivalent of recycling endosomes or late endosomes in T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…This would require packaging of the maturase into the nascent micronemes where processing would occur in a manner akin to prohormone convertase processing of substrates in immature secretory granules (ISGs) (Molinete et al, 2000;Hook and Metz-Boutigue, 2002). A distinction here, however, is that ISGs are derived from condensing vacuoles that bud from the TGN (Natori et al, 1998). Alternatively, if the proTgM2AP-positive compartment is distinct from early endosomes, its juxtaposition suggests that it might be the equivalent of recycling endosomes or late endosomes in T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many of the experiments performed in endocrine cells to define sorting mechanisms and signals are not possible in primary parotid cells or tissue culture. Regulated secretory proteins are typically sorted to the regulated secretory pathway in foreign secretory cells (Burgess et al, 1985;Natori et al, 1998). Thus, the study of salivary protein secretion in non-salivary cells may provide information on protein-specific processes, although caution is warranted due to differences between cell types (Gorr et al, 2001).…”
Section: (Iv) Secretion Of Salivary Proteins From Non-salivary Cell Tmentioning
confidence: 99%
“…For expressing proteins in a wide variety of tissues, a CMV promoter can be used. In addition, our own observations (see below) and the data from Natori et al [1] showed that using a CMV promoter can result in a highly specific protein expression in exocrine pancreatic acini. Gene-targeted mice are derived from embryonic stem (ES) cells.…”
Section: Introductionmentioning
confidence: 66%